2022
DOI: 10.1186/s13063-022-06461-z
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the impact of a novel house design on the incidence of malaria in children in rural Africa: study protocol for a household-cluster randomized controlled superiority trial

Abstract: Background Traditional rural housing in hot, humid regions of sub-Saharan Africa usually consists of single-level, poorly ventilated dwellings. Houses are mostly poorly screened against malaria mosquitoes and limited airflow discourages the use of bednets resulting in high indoor transmission. This study aims to determine whether living in a novel design house with elevated bedrooms and permeable screened walls reduces malaria, respiratory tract infections, and diarrhoea among children in rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This study is subject to several limitations. Our characterization of housing was constrained by the availability of data from household surveys, which generally only ask about just three components, and don't include questions about other relevant features of the built household environment, such as screens covering openings [62] elevation of sleeping areas or improvements to windows and ventilation [63]. Although the variables were originally in three-class ordinal categorical format, we had to combine categories and model them as dichotomous, because there is currently no way to address adjacent categories and parallel odds using the INLA modeling approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is subject to several limitations. Our characterization of housing was constrained by the availability of data from household surveys, which generally only ask about just three components, and don't include questions about other relevant features of the built household environment, such as screens covering openings [62] elevation of sleeping areas or improvements to windows and ventilation [63]. Although the variables were originally in three-class ordinal categorical format, we had to combine categories and model them as dichotomous, because there is currently no way to address adjacent categories and parallel odds using the INLA modeling approach.…”
Section: Discussionmentioning
confidence: 99%
“…enter the home through eaves and other openings [64] and rest on walls and ceilings after ingesting a blood meal (the basis behind indoor residual spraying [IRS] of these surfaces as a malaria control intervention). Indeed, in Africa, 80% of malaria transmission occurs indoors [3] and houses with roofs and walls constructed of natural material provide more points of entry [64,65] and preferred resting places [66] for malaria-transmitting mosquitoes, insights which are increasingly putting housing improvements on the research agendas as potential disease control strategies [63,65]. In rural Gambia, studies have found reductions in intradomiciliary mosquito vector abundance and survival through installing plywood ceilings [67], closing eaves in thatched roofs [68,69], and replacing thatch with ventilated metal roofing [70].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing ventilation, which dilutes the carbon dioxide, will have the opposite effect reducing house entry by An. gambiae [ 100 , 101 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Based on the pilot study and taking into account the preferences of residents, the team designed a novel healthy house and set out to run a RCT in rural Tanzania. The new 'Star Home' was designed to protect against three diseases of childhood, responsibility for great childhood mortality in sub-Saharan Africa: malaria, diarrhoea and acute respiratory tract infections [8,9]. Using data from the national malaria control programme and after fact-finding visits, Mtwara Region in south-east Tanzania was selected as a study site: in contrast to the pilot study site in Tanga, malaria transmission remained high and there were few other ongoing and planned health-related studies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite funding and logistical challenges, by early 2021, the construction of 110 Star Homes had been completed across 60 villages in Mtwara Region. With strict eligibility criteria that targeted the poorest families in the communities, households had been selected based on a lottery system [9]. Keys were handed over to the lottery winners (who had been consulted throughout construction) and the study staff were ready to begin assessing the health impact of these new homes.…”
Section: Introductionmentioning
confidence: 99%